Northern old industrial regions: breaking the path in resource development - Alexander Pelyasov; Natalya Galtseva (European Regional Science Association (ERSA), 2012)
The major reason of economic depression of old industrial regions is the aging of their economic structure and loss of competitive advantages of their basic sectors. Not the sectors of the regional economy are getting old but determined by economic age conditions of their development in the concrete region. Indicators of basic sectors getting old can be production of non-competitive output because of backward technique and technology, ineffective organization of the industrial process etc. It is possible to include in the list of old industrial regions not only manufacturing but also resource-dependent regions like Magadan Oblast in the North-East of Russia. Resource regions have distinct specificity in their aging: it is general decrease in the quality of extracted resources and lack of technology to utilize depleted resources. Generally the main directions of the restructuring of the economy of the old industrial regions are diversification, introduction of product, process and organizational innovations and elaboration of new competencies. Magadan Oblast in the North-East of Russia has been developed its gold deposits for more than 80 years. So it can be regarded as Northern resource old industrial region. And its directions of economic restructuring lie in resource diversification, technological and institutional innovations, and new economic competencies of the labor force. Efficiency of each direction of regional economic restructuring is measured by indicators of GRP, employment, and real income. At the result of different combination of the projects in the three directions of restructuring one can characterize four scenarios for Magadan Oblast future development. The first is connected with the introduction of innovation in the existing resource projects. The second includes existing and new projects connected with coal deposits. The third includes the projects from the previous scenarios plus project of diversification connected with elaboration of tin and tungsten deposits. This scenario can help Magadan Oblast to come into the group of Russian regions with the average level of economic and social development. And finally fourth scenario related to the large-scale exploitation of the off-shore oil and gas deposits can help to change radically the economic specialization of the region and increase rates of economic growth of the previously territory of economic depression.
Keywords: 330